Two Monogenetic Disorders, Activated PI3-Kinase-δ Syndrome 2 and Smith–Magenis Syndrome, in One Patient: Case Report and a Literature Review of Neurodevelopmental Impact in Primary Immunodeficiencies Associated With Disturbed PI3K Signaling - Moreno-Corona, Nidia; Chentout, Loïc; Poggi, Lucie; Thouenon, Romane; Masson, Cecile; Parisot, Melanie; Mouel, Lou Le; Picard, Capucine; André, Isabelle; Cavazzana, Marina; Perrin, Laurence; Durandy, Anne; et al. (Frontiers in Pediatrics, 2021)
Activated PI3-kinase-δ syndrome 2 (APDS2) is caused by autosomal dominant mutations in the PIK3R1 gene encoding the p85α, p55α, and p50α regulatory subunits. Most diagnosed APDS2 patients carry mutations affecting either the splice donor or splice acceptor sites of exon 11 of the PIK3R1 gene responsible for an alternative splice product and a shortened protein. The clinical presentation of APDS2 patients is highly variable, ranging from mild to profound combined immunodeficiency features as massive lymphoproliferation, increased susceptibility to bacterial and viral infections, bronchiectasis, autoimmune manifestations, and occurrence of cancer. Non-immunological features such as growth retardation and neurodevelopmental delay have been reported for APDS2 patients. Here, we describe a patient suffering from an APDS2 associated with a Smith–Magenis syndrome (SMS), a complex genetic disorder affecting, among others, neurological manifestations and review the literature describing neurodevelopmental impacts in APDS2 and other PIDs/monogenetic disorders associated with dysregulated PI3K signaling.